Nuevas localidades en la distribución geográfica de Diaemus youngii y Macrophyllum macrophyllum en la vertiente del Pacífico Mexicano - Pozo-Montuy, Gilberto; López Hernández, Jorge Alberto; Candelaria Peña, Arturo; Castro Luna, Alejandro Antonio (Therya Notes, 2025)
Diaemus youngii and Macrophyllum macrophyllum are present in Mexico. They have a marginal northern distribution in the country and have few records. The objective was to expand the geographical distribution of D. youngii for the Mexican Pacific slope in Chiapas and add records of M. macrophyllum in this area. Sampling was carried out in three periods: December 2020, May 2021 and July 2022 in the Municipality of Villa Comaltitlán, Chiapas. There were seven nights per period with 3 mist nets placed within the vegetation, near the Papagayo River and an oil palm plantation. The sampling effort was 252 hr and 386 records of bats were obtained, belonging to 12 species, including D. youngii and M. Macrophylla. One adult male individual of D. youngii and four of M. macrophylla were obtained. A fifth record occurred accidentally on the Pijijiapan-Tonalá highway with a road-killed individual. The record of D. youngii in this study is the first for the Pacific coast of the state of Chiapas. The record was located more than 197 km in a straight line from the nearest capture site, Chajul, Chiapas. The records of M. macrophylla complement previous records for the Pacific slope of Chiapas. Diaemus youngii and M. macrophyllum are considered uncommon throughout their distribution and with few records in biological collections in Mexico. The contribution of the new records of both species in this study is valuable to complement the knowledge of their distribution.